EPIDEMIOLOGY OF INJURIES OF THE MAXILLOFACIAL REGION IN THE KEMEROVO REGION - KUZBASS - Руслан Викторович Меллин; Константин Анатольевич Сиволапов; Николай Васильевич Малков; Мария Сергеевна Малых; Вадим Гельевич Мозес (Медицина в Кузбассе, 2020)
The article presents an epidemiological analysis of injuries of the maxillofacial region in the Kemerovo region, which made it possible to clarify the prevalence of this pathology and to reveal the peculiarities of the medical consequences of injuries among residents of the region.